Perceptions of challenges in writing academically: Iranian postgraduate students’ perspectives - Kotamjani, Sedigheh Shakib; Hussin, Habsah (Flourishing Creativity & Literacy, 2017)
Academic writing skills are essential tools that postgraduate students reading for their doctoral degree have to master to be able to produce dissertations, research reports and academic assignments of quality in the course of their studies; and publish research-based articles in established journals. This paper discusses the perceptions of a group of Iranian postgraduate students pursuing their doctoral degrees at UPM (Universiti Putra Malaysia) on the challenges they face in writing academically. They provided the data for this paper via their responses to a survey. The findings indicate that these postgraduate students perceived some academic writing skills to be more challenging than the others. The paper concludes with a discussion on the implications of the findings; and recommendations on how the situation can be improved.